2014
DOI: 10.6001/energetika.v60i2.2935
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for stakeholders in renewable energy investments

Abstract: Modern economic development is based on innovative ideas and new investments. The better resources are deployed in investment projects, the higher the level of innovation and return for the soci ety. On the other hand, both the efficiency of investment activities and the pace of economic growth are, to a great extent, conditioned by the quality of the system of selecting investment projects, which correspond to the existing and changing circumstances of econom ic functioning. The paper aims to identify and ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“… Sources: Diógenes et al (2019), Zhao et al (2019), Islam et al (2018), Guo et al (2018), Liu et al (2018), Loannou et al (2017), Xinyao et al (2017), Macchiaroli et al (2017), Rolik (2017), Tavakolan and Etemadinia (2017), Angelopoulos et al (2017), Noothout et al (2016), Guerrero-Liquet et al (2016), Gatzert and Kosub (2016), Li and Li (2015), Gang (2015), Jankauskas et al (2014), Jin et al (2014), Michelez et al (2011) and De Jager et al (2008). …”
Section: Resultsmentioning
confidence: 99%
“… Sources: Diógenes et al (2019), Zhao et al (2019), Islam et al (2018), Guo et al (2018), Liu et al (2018), Loannou et al (2017), Xinyao et al (2017), Macchiaroli et al (2017), Rolik (2017), Tavakolan and Etemadinia (2017), Angelopoulos et al (2017), Noothout et al (2016), Guerrero-Liquet et al (2016), Gatzert and Kosub (2016), Li and Li (2015), Gang (2015), Jankauskas et al (2014), Jin et al (2014), Michelez et al (2011) and De Jager et al (2008). …”
Section: Resultsmentioning
confidence: 99%
“…The risk factors included in the study was based on the risk registers proposed by Zou et al . (2012), Holburn (2012), Jankauskas et al . (2014), Gatzert and Kosub (2015), Mosannenzadeh et al .…”
Section: Methodsmentioning
confidence: 98%
“…The authors suggested that besides insurance, diversification is one of the important tools for risk mitigation. Jankauskas et al . (2014) identified and assessed risks factors of renewable energy investment projects from the perspective of stakeholders.…”
Section: Previous Studiesmentioning
confidence: 99%
“…The topics of risk, uncertainty and information have been always crucial in economics (Knight 1921;Hirshleifer, Riley 1992;Ching, Colombo 2014;Iglesias-Casal et al 2016;Chen et al 2017). There is no field in economics in which risk is not an important dimension of the decision-making environment (Gollier 2001;Taleb 2010;Chen, Zhang 2014;Rudzkis 2014;Jankauskas et al 2014;Zeng et al 2017). There is a small amount of decisions that can be taken in the situation of complete certainty.…”
Section: Introductionmentioning
confidence: 99%